2009
DOI: 10.1523/jneurosci.1636-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Unpredictable: Weighted Averaging of Past Stimulus Timing Facilitates Ocular Pursuit of Randomly Timed Stimuli

Abstract: In motor control, prediction of future events is vital for overcoming sensory-motor processing delays and facilitating rapid and accurate responses in a dynamic environment. In human ocular pursuit this is so pervasive that prediction of future target motion cannot easily be eliminated by randomizing stimulus parameters. We investigated the prediction of temporally randomized events during pursuit of alternating constant-velocity (ramp) stimuli in which the timing of direction changes varied unpredictably over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 40 publications
(46 reference statements)
8
42
0
Order By: Relevance
“…Participating subjects do not know when the step or ramp part is going to occur, and therefore, there is a tendency to compensate more with saccadic movement even in case of the ramp stimulus. This hypothesis is supported, in part, by evidence that the properties of the previous stimulus affect HOS performance during the current task (Collins & Barnes, 2009). Another explanation is possible fatigue due to the fact that the stimulus explored here was presented as the last task in a sequence of other tasks, even though the whole sequence of tasks was designed not to cause excessive fatigue.…”
Section: Variability Of Hos Performancementioning
confidence: 64%
“…Participating subjects do not know when the step or ramp part is going to occur, and therefore, there is a tendency to compensate more with saccadic movement even in case of the ramp stimulus. This hypothesis is supported, in part, by evidence that the properties of the previous stimulus affect HOS performance during the current task (Collins & Barnes, 2009). Another explanation is possible fatigue due to the fact that the stimulus explored here was presented as the last task in a sequence of other tasks, even though the whole sequence of tasks was designed not to cause excessive fatigue.…”
Section: Variability Of Hos Performancementioning
confidence: 64%
“…Rather, we contend that the nervous system predicts (using an internalized dynamical E. Roth and others model) the movement of the exogenous signal. Similar stimulus prediction has been described in terms of probabilistic representations of target locations in a pointing task (Körding and Wolpert, 2006) and in terms of the anticipation of the time of direction reversal in a visual target tracking behavior (Collins and Barnes, 2009). …”
Section: An Internal Model Predicting Refuge Movement Explains Phase mentioning
confidence: 93%
“…For example, despite substantial visuomotor delays, SPEMs can achieve zero phase lag with respect to target trajectories and persist even during target blanking (Orban de Xivry et al, 2008). In tracking horizontal piecewise-constant velocity trajectories (irregular triangle waves in position) human subjects change eye velocity in anticipation of target turnaround; Barnes and Collins proposed that the behavior incorporates a model for expected (or minimum) turnaround times (Collins and Barnes, 2009). Orban de Xivry et al observed that while tracking a circular trajectory with target blanking, smooth pursuit and catch-up saccades occurred during blanked periods and explained the phenomena as a result of predicted target dynamics based on a 'velocity memory' (Orban de Xivry et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the latency of pursuit onset can be shortened and the eyes can even start moving before the target (Kowler et al 2014). Anticipatory smooth pursuit can be induced by the repeated presentation of the same motion trajectory (Kowler and Steinman 1979), by a prior cue indicating the target motion direction (de Hemptinne et al 2008), by the history of recent trials (Collins and Barnes 2009), or when the target motion is generated by the observers themselves (Steinbach 1969). …”
Section: Humans Often Have To Track Motion That Is Generated By Themsmentioning
confidence: 99%
“…Toward this aim, we took advantage of the lateralized readiness potential (LRP) component, a negative-going potential, which can be observed over the contralateral motor areas before a manual response is produced (for an overview, see Smulders and Miller 2012). The LRP starts shortly (300 -500 ms) before the voluntary movements and is assumed to be generated within the primary motor area (e.g., Coles 1989;de Jong et al 1988). The LRP has been widely used to assess motor preparation and organization (e.g., Hackley and Miller 1995;Low et al 2002;Miller and Low 2001).…”
Section: Humans Often Have To Track Motion That Is Generated By Themsmentioning
confidence: 99%